2017
DOI: 10.1515/jpem-2016-0152
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of sex development in children in KwaZulu-Natal Durban South Africa: 20-year experience in a tertiary centre

Abstract: DSD is not an uncommon diagnosis in African patients in sub-Saharan Africa. The most common aetiological diagnosis is 46 XY DSD in androgen synthesis and action, followed by ovotesticular DSD. CAH is only the third most common disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 18 publications
7
29
3
Order By: Relevance
“…The frequency of OT DSD is high amongst Black South Africans [2]. Although this finding may appear biased, it is important to note that this cohort was extracted from a database of patients with DSD which reflects the different population groups in South Africa [4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of OT DSD is high amongst Black South Africans [2]. Although this finding may appear biased, it is important to note that this cohort was extracted from a database of patients with DSD which reflects the different population groups in South Africa [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Wiersma and Ramdial [3] reported that more than half of the number of patients (51%) presenting to a single paediatric surgical unit in KwaZulu-Natal (KZN) (Durban) had OT DSD. We recently reported that 22% of the patients with DSD attending a tertiary endocrine unit in KZN had OT DSD [4]. This is disproportionately high compared to other centres worldwide [5].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that CAH was the third most common diagnosis in children with DSD attending a specialised endocrine unit. [4] In 2008, Osifo and Nwashilliv [5] retrospectively reported on 27 children with CAH in Nigeria, highlighting the challenges of managing these children in a developing country. Tayel et al [6] reported a high prevalence of CAH in Alexandria, Egypt, justifying the need for a newborn screening programme.…”
Section: Researchmentioning
confidence: 99%
“…Mortality and morbidity is likely underreported because clinical features of pediatric endocrine diseases and of diabetes may mimic infections and other common medical conditions, causing misdiagnosis [39, 40]. In addition, a complete neonatal examination is not routinely performed in many settings, preventing the diagnosis of congenital conditions such as disorders of sexual development [13, 41]. It is expected that the increase in capacity in pediatric endocrinology will lead to a better understanding of the prevalence and characteristics of pediatric endocrine diseases and diabetes which, in turn, will drive advocacy for essential medicines that are presently not available to the patient.…”
Section: Discussionmentioning
confidence: 99%